Remote sensing of open-air landfills of municipal solid waste in a province of Tacna - Mendoza Aquino , Marisol (2023)
Remote sensing played a crucial role in the study by facilitating the collection of essential data for monitoring and creating interactive maps detailing the locations of open-air municipal solid waste landfills in the Tarata Province. This approach allowed for a comprehensive understanding of the distribution and characteristics of the landfills. Using ArcMap software, a comparison was conducted between the 2023 and 2016 data. The process involved the examination of satellite images and georeferenced records. Additionally, a set of orthophotos captured by a drone was integrated into the study. These analyses resulted in the identification of four landfills. The largest one, covering an area of 1568.02 m2, was found in Ticaco, highlighting the magnitude of the waste disposal issue in this area. Conversely, the smallest one, covering an area of 378 m2, was discovered in Estique. Furthermore, the evaluation of the images revealed soil degradation over time, which was particularly evident in the orthophoto captured by the drone. This stands out the environmental impact of landfill activities. Ultimately, the use of remote sensing and drone technology provides valuable information for making informed decisions and managing waste sustainably in the region.